Prevalence of mental health status among displaced individuals at Hamam al-Alil camp in Ninevah governorate - Mohammed Baktash; Iman Jallod (University of Mosul-college of Basic Education, 2024)
Background: Nearly 45 million individuals worldwide are internally displaced annually by conflicts. While the psychological effects of war have been extensively documented, there is less understanding of the psychological and mental health symptoms experienced by internally displaced persons (IDPs) as a result of forced displacement. (IDPs). Aim: This study aims to assess the mental health status of people displaced in Hamam Al-Alil Camp. Methods: The cross-sectional survey study design was performed in Hamam Al-Alil camps (Situated on the western bank of the Tigris River in the Nineveh Governorate in Iraq, to the south of Mosul) for the period of 26th December 2017 throughout 1st March 2018. The sample of the study consists of (869) participants. Results: The study distributed 869 surveys which show that the estimation of females was (54%), while males (46%), most of the participants in this study were at age (18-30) years old, and a majority of the participants reported at least one or more mental conditions such as PTSD and anxiety  Conclusions: Most of the participants were female and housewives (54%) (52%) respectively, and in terms of age (39%) they ranged in age from 18 to 30 years old as well as Hamam Al-Alil residents people reported a high prevalence of mental health symptoms. Recommendation: Resettlement partners must be mindful of the specific health concerns within this population to effectively meet the needs of the community.